Existential Dimensions of Subjective Social Well-Being of the Individual - Halian , Ihor; Halian , Andrii (Insight: the psychological dimensions of society, 2025)
The aim of the study is to explore existential experiences within the structure of an individual’s subjective social well-being. It is hypothesized that one of the determinants of subjective social well- being is a sense of existential fulfillment, expressed through self-distancing, self-transcendence, and a striving for freedom and responsibility. Methods.The research is grounded in the principles of existential-humanistic psychology. Subjective social well-being was assessed using the questionnaire “Subjective Social Well-Being” (Danylchenko, 2015). Existential fulfillment was measured using the “Existence Scale” (Längle & Orgler, 2009). The study was conducted using a post-factum design to predict the influence of independent variables on the dependent variable. Statistical analysis of the results was performed using correlation and linear multiple regression methods. Results. The level of existential fulfillment among respondents was diagnosed, and the share of predictors contributing to the formation of their subjective social well-being was determined. The most sensitive dependent variable, reflected in the “Subjective social well- being index” showed the strongest correlation with the predictor “Self-transcendence”. “Freedom” as an indicator of existentiality also proved to be a significant predictor. The least represented component in the structure of subjective social well-being was “Self-distancing”. All predictors of subjective social well-being in the model were statistically significant at p < .010. The surveyed youth demonstrated a low capacity for “self-transcendence”, indicating emotionally impoverished relationships and a pragmatic, functionally oriented mindset. A low score for “freedom” reflected a tendency to avoid decision- making and hesitation due to anxious expectations about potential outcomes. Dependence on affect and bias was expressed through a low level of “self-distancing”. Discussion and conclusions. The study confirmed the hypothesis that existential experiences are fundamental to the formation of subjective social well-being. Using multiple regression analysis, the influence of self- distancing, self-transcendence, and freedom on the emergence of subjective social well-being was predicted. Exploring the relationship between subjective social well-being and personal qualities within a Ukrainian sample presents a promising direction for further empirical research in this area.